Mechanical properties of all-C/C composite hybrid bonded/bolted joints. (April 2023) - Tang, Yuling; Ren, Yuhe; Zhao, Wei; Zhou, Zhengong; Han, Lu
In this paper, experiments and numerical simulations were used to study the mechanical properties of all-C/C composite hybrid bonded/bolted joints. Experiments were conducted to investigate the failure mechanisms, modes, and strengths of composite single-lap joints, namely, bolted joints with and without bonds. The results demonstrated that the failure mode of all-C/C composite mechanical joints was bolt shear failure, while the failure mode of the bonded joints was cohesive force failure. In hybrid bonded/bolted joints, cohesive force failure of the adhesive layer and bolt shear failure have both been noted. The C/C composite plates of all joints were not discovered to have any evident deterioration. The load-displacement curve of the hybrid joints was a double-peak curve, the first peak load corresponds to bonding failure, and the second peak load corresponds to bolt failure. For the failure process, mode, and strength of hybrid (bonded/bolted) joints, a 3D progressive damage finite element model was proposed. It is based on the nonlinear finite element code ABAQUS and Hashion failure criteria. The VUMAT subroutine compiled Hashion failure criteria to simulate the damage of fiber and matrix in the composite material. Furthermore, the adhesive layer's failure was simulated using the cohesive element. Comparing failure loads and failure modes to the outcomes of experiments served to validate the model. The gradual damage evolution process and failure mechanism of bonded and hybrid bonded/bolted joints were determined, as well as the mechanism by which the cohesive layer influences the mechanical properties of the hybrid bonded/bolted joints. On the mechanical characteristics of composite joints, the impacts of bolt diameter and adhesive layer modulus were investigated.